Film as a Form of Cultural Medium: Trends of the Film Industry - Gao, Yunlin (Transactions on Social Science, Education and Humanities Research, 2024)
As an important form of entertainment, this paper delves into global cinema, analyzing the significant factors that have shaped the patterns people watch and evaluate films in recent years. The paper focuses on three primary dynamics: the COVID-19 pandemic, the diminishing qualities of movies themselves including the proliferating numbers of remakes and sequels, a perceived decline in film quality attributed to Hollywood’s emphasis on political correctness, as well as the emergence of streaming services and short video applications. The epidemic has greatly transformed the conventional practice of seeing movies in theaters, expediting the transition to digital platforms. Simultaneously, there is widespread discontent among people over the current standard of movies. The emergence of streaming and platforms for short-form material has caused the audience to become more divided, providing a wide range of options for viewing and posing a challenge to the traditional cinema model. The complex interplay between these forces and their collective influence on the future of film as a cultural and entertainment medium.